The effect of zinc sulfate supplementation on the growth factor Amphiregulin in the human adenocarcinoma cell line Caco-2 - Åströms, Marianne (My University, 2022)
Iron deficiency and iron deficiency anemia is a worldwide health problem. In 2016 one billion people worldwide suffered from iron deficient anemia. To treat or prevent iron deficiency, iron can be added to the diet as supplements or directly to food. One additive approved by the European Food Safety Authority for use in foods is ferric EDTA. Unfortunately, ferric EDTA has been observed to induce the cancer marker Amphiregulin in human cell studies and increase tumor burden in mice studies. Ferrous sulfate did not affect amphiregulin induction in human cell studies suggesting that the effect is connected to the affinity of iron to its ligand and therefore also the binding of iron to its transport protein at the site of absorption in intestinal cells. Zinc salts have been observed to interfere with iron uptake by its transporter DMT1 in intestinal cells. We therefore sought to investigate if zinc sulfate could affect the induction of amphiregulin in the presence of ferric EDTA. The human intestinal Caco-2 cell model, validated for iron absorption studies, were incubated with three different iron compounds (500µM); ferric chloride, ferric EDTA and ferrous fumarate alone and together with zinc sulfate (20 and 100µM). The cell lysates were then analyzed to predict cell survival and amphiregulin production. All treatments induced amphiregulin compared to control; ferric EDTA (316% ±74%), ferric EDTA + zinc sulfate 100µM (252% ±50%), ferric chloride (157% ±43%), ferric chloride + zinc sulfate 100µM (157% ±43%), zinc sulfate 100µM (143% ±19%), ferrous fumarate (120% ±8%), ferrous fumarate + zinc sulfate 100µM (120% ±15%). In this study ferric EDTA increased amphiregulin levels 3.8-10.8-fold compared to the other treatments but there was no effect of zinc sulfate (20µM and 100µM) on amphiregulin levels in the presence of ferric EDTA, ferric chloride or ferrous fumarate at 500µM. Ferric chloride (500µM) was the only treatment showing a lower cell survival compared to control, ferric chloride (82% ±10%). In conclusion, zinc sulfate at the given concentrations did not lower amphiregulin induction in the presence of ferric EDTA at 500µM
Keywords: Zinc sulfate; Amphiregulin; Dietary supplements; Caco-2 cells; Ferric EDTA